Prospective adherence to specific immunotherapy in Europe (PASTE) survey protocol. Issue 1 (27th April 2015) - Makatsori, Melina; Senna, Gianenrico; Pitsios, Constantinos; Lleonart, Ramon; Klimek, Ludger; Nunes, Carlos; Rukhadze, Maia; Rogala, Barbara; Gawlik, Radoslaw; Panzner, Petr; Pfaar, Oliver; Calderon, Moises
Abstract: Background: Adherence to allergen immunotherapy is important for its effectiveness. There is currently limited data available on allergen immunotherapy adherence outside of clinical trials i.e. in real‐life clinical practice. As part of a European Academy of Allergy and Clinical Immunology Immunotherapy Interest group initiative, we endeavoured to design a survey in order to prospectively evaluate adherence to subcutaneous and sublingual immunotherapy across different European countries. Method/Design: The inclusion criteria for this prospective, multi‐country survey were set as: adults, starting clinically indicated allergen immunotherapy for respiratory allergic disorders or Hymenoptera venom allergy. An online survey was designed in order to enrol participants and assess adherence to immunotherapy. Eight countries (Czech Republic, Georgia, Germany, Greece, Italy, Poland, Portugal, Spain) were selected to reflect different parts of Europe and differences in allergens and routes of immunotherapy administration. Each country has an allocated National co‐ordinator that has identified local Allergy departments willing to enrol participants in this survey. Each participant will be followed up for a total of three years. In order to assess adherence, a 4‐monthly follow‐up form detailing any missed doses and reasons will be completed online. In case of a participant discontinuing treatment, reasons for this will be recorded. Discussion: The use of online survey software has enabled us to make this survey a reality and reach clinicians in different countries. Forty‐five centres have enrolled a total of over 1, 350 participants. It is hoped that this prospective real life survey will enable us to gain a better understanding of reasons that affect adherence to subcutaneous and sublingual immunotherapy and assist in developing ways to improve this.